Niveles de expresividad de la fuerza: una propuesta de sistematización de la ontología leibniziana - Escribano, Miguel (2014)
Along with the logicist line of interpretation, the dynamic one has been one of the most privileged in the history of the reception of Leibniz’ work. This is due to the fact that related to the semantic field of the notion of force we find several of the main problems which stimulate the development of philosophical thinking in its ontological dimension. An analytical approach which takes as basis the abstract model of force reestablishes the limits of dynamics, at least as it is found nowadays in the science of physics, and emphasizes within Leibniz’ work the interplay of a multitude of speculative fields as well as the internal logic of the discipline. It is Leibniz himself who situates the notion of dynamics in direct relationship with metaphysics.